The influence of attitudes toward ecopreneurship on ecopreneurship intention: A study on generation Z students in Bandung city - Wakan, Fadlina Nova Aisyah; Hatammimi, Jurry (Edelweiss Applied Science and Technology, 2025)
Indonesia’s high youth unemployment and environmental degradation call for innovative, sustainable solutions. This study aims to examine how attitudes influence ecopreneurship intention among Generation Z students in Bandung City, Indonesia. Grounded in the Theory of Planned Behavior (TPB), the study focuses on both instrumental and affective dimensions of attitude. A quantitative approach was employed using a cross-sectional survey method, with data collected from 400 respondents selected through purposive sampling. Simple linear regression analysis was conducted to examine the relationship between variables. The findings reveal a significant and positive influence of attitude toward ecopreneurship on ecopreneurship intention. These results confirm the TPB assumption that attitude is a key determinant of behavioral intention. The study concludes that Generation Z students who perceive ecopreneurship as valuable, both economically and personally, are more likely to pursue sustainable entrepreneurial ventures. This research offers practical implications for educational institutions and policymakers by emphasizing the importance of fostering green attitudes among youth. Curricula that integrate ecopreneurial values and government-supported training or funding programs could enhance sustainable entrepreneurship in Indonesia’s younger population.